A Massive Right Atrial Myxoma - Haque, SM Shahidul; Hasan, Syed Mainul; Khan, M Amiruzzaman (Pulse, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20361 Pulse Vol.6 January-December 2013 p.79-83